Odpowiedzi

Najlepsza Odpowiedź!
2010-02-03T20:55:34+01:00
an=an-1 × q czyli nastepny wyraz obliczasz mnozac przez q ten wczesniejszy
a) a2 = 1 x 3= 3
a3 = 3 x3=9
a4=9 x3= 27
a5= 27x3=81

b) a2 = 16 x 0,5 =8
a3=8 x 0,5 = 4
a4=4x0,5=2
a5=2x0,5=1

c)a2=5x(-1)= -5
a3 = (-5) x (-1) = 5
a4= 5x(-1)= -5
a5 = (-5) x (-1) = 5

d)a2=1/4 x (-2) = -1/2
a3 = (-1/2) x (-2) = 1
a4 = 1 x (-2) = (-2)
a5 = (-2) x (-2) = 4
1 5 1
2010-02-03T21:09:44+01:00
A) a₁=1 , q=3 a₂=3 a₃=9 a₄=27 a₅=81
b) a₁=16 , q=½ a₂=8 a₃=4 a₄=2 a₅=1
c) a₁=5 , q= -1 a₂=-5 a₃=5 a₄=-5 a₅=5
d) a₁=¼ , q= -2 a₂=-1/2 a₃=1 a₄=-2 a₅=4
1 3 1